Arteriovenous Fistula for dialysis – Let's Google it. Readability and quality of online information. Issue 1 (February 2021) - Bresler, Richard M.; Lynch, Noel P.; Connolly, Mary; Keelan, Stephen; Richter, Louis; McHugh, Seamus M.; Naughton, Peter A.
Abstract: Background: This study evaluated the readability and quality of information regarding arteriovenous (AV) fistula for dialysis on the Internet in the English language. Study design: Using Google© search, the keywords "AV Fistula for dialysis" were searched. The top 75 ranking sites were analyzed. One website was excluded due to repetition. Each landing page was assessed independently by two authors (RB, LR) for readability using the Flesch Reading Ease Score (FRES) and Gunning Fog Index (GFI). Web site quality was assessed using the DISCERN instrument. The individual position of the top 15 websites in the search engine ranking order list was noted. The country of origin, organization type and issuance of Health on the Net (HoN) Certification was recorded. Statistical analyses were performed using unpaired t-tests and ANOVA variance. Results: The mean GFI score was 9.2 and the mean FRES score was 50.6, indicating poor readability. The mean DISCERN score was 48.4, indicating weak quality of websites. Website quality was influenced by the academic/healthcare organization type (p = 0.012). Organization type was not found to impact GFI and FRES scores. Presence of a HoN Certification was not found to impact the quality of information. The majority of sites originated from the United States (61%). Conclusion: Our study demonstrates that internet information pertaining to AV fistula for dialysis is of poor quality necessitating improvements to readability and overall website quality to improve the patient experience. Further research into how to improve healthcare web information is needed.